EVALUASI KINERJA DAN PERKUATAN STRUKTUR GEDUNG GUNA ALIH FUNGSI BANGUNAN (Studi Kasus : Perubahan Fungsi Ruang Kelas Menjadi Ruang Perpustakaan Pada Lantai II Gedung G Universitas Semarang) - Christiawan, Ignatius; Triwiyono, Andreas; Christady, Hary (Civil Engineering Forum Teknik Sipil, 2008)
To meet the need for good infrastructure of building construction, building new one is not theonly appropriate choice. Efficiency resulted from the functional substitution of existing building to be used with a new function can be a more precise alternative. The existing functional substitutio will result in the change of the building load. Based on the fact, it is necessary to evaluate the performance and the strength of structure at the existing condition to take new load and to calculate the strengthening required. The study is conducted on Building G of Campus III, Semarang University at Jl.Soekarno- Hatta, Semarang. A lecturing space in floor II was proposed to be functionally substituted into library room. It focuses on evaluating performance of structure, the strength of plate, beam, and column, and the bearing of foundation, existing condition based on SNI-2847-2002, earthquake load application based on SNI-1726-2002, and promoting a proposal for strengthening the structure required. The SAP 2000 is used to analyze the structure to gain the required strength value of U (ultimate). BETON 2000 is used to analyze the structure of existing condition to gain the existing strength value of R (resistance). The strengthening of the plate and beam is conducted by adding the Fiber Reinforced Polymer (FRP), while that of column is by adding an external reinforcement The result of the study indicates that the existing fc’ is 17 MPa and the fy is 390 MPa. From evaluation on the performance of structure, it can be known that the performance of servicing limit and that of ultimate limit of the building have really met the requirement of SNI-1726-2002. Based on the result of analysis on the structure of plates in floor 2, plates of A, C, E, and H need the strengthening of flexure ability. Beam in floor 2 : 1 A-E ; 1 E-I ; 2 A-E ; 2 E-I ; 3 C-E and ring beam : 0 A-C ; 0 C-E ; 0 E-G ; 0 G-I ; 3 C-E ; 3 E-I require the strengthening of flexure ability and shear ability. The strengthening of flexure and shear abilities by adding the FRP is found to be able to add the flexure and shearing abilities of plates and beam. The result of analysis on the strengthening of flexure ability by adding reinforcement shows that it can add the flexure ability of column. And form analysis on foundation, it can be known that foundation is able to bear new load so it does not require the strengthening.